Discourse on Hudud in Malaysia: addressing the missing dimension - Haneef, Sayed Sikandar Shah (Routledge, 2010)
A great deal has been written on the issue of applicability of hudud law in Malaysia. But, by and large, the discourse revolves around the feasibility or otherwise of its implementation in the context of the existing legal framework by both local academia and politicians. Little attention has been paid to the question of the type and model of hudud that need to be enacted into laws. This study argues that the discourse on hudud would not be complete unless hard questions surrounding its substance and practical procedures are judiciously disposed.